Social media sharing, psychological distress, and student well-being: a PLS-SEM and fsQCA analysis of Chinese college students - Shu, Bo; Dong, Zhigao; Su, Fang; Wang, Zheng (Frontiers in Psychology, 2025)
This study explores the relationship between social media sharing behavior and the mental health and well-being of college students. Based on the Digital Well-being Theory, we applied PLS-SEM and fsQCA to analyze data from 534 students across two time points. Results show that school-related (β = 0.198, p < 0.05) and social-related (β = 0.234, p < 0.05) social media sharing behaviors positively impact well-being, while work-related sharing (β = 0.247, p < 0.05), though also positive, can increase psychological distress. Psychological distress significantly reduces well-being and mediates the relationship between social media sharing and well-being. However, perceived support effectively moderates this effect, reducing the negative impact of psychological distress on well-being. FsQCA analysis identified multiple combinations of factors leading to higher well-being, emphasizing the importance of considering diverse influences (fsQCA coverage = 60.01%). The study provides practical insights for educators, policymakers, and students on using social media to promote mental health and well-being.